KEARIFAN EKOLOGIS DALAM CERITA RAKYAT DAYAK BAKUMPAI: KAJIAN EKOKRITIK - Hestiyana Hestiyana (HISKI, 2021)
This study aims to describe ecological wisdom in Bakumpai Dayak folklore using the theory of literary eco-criticism. This research method is descriptive qualitative. The source of the data in this study is the text of the Collection of Bakumpai Folklore. The data used are texts in folklore that focus on literary and environmental aspects entitled (1) “Mang Raja Haji dan Tujuh Orang Putri” and (2) “Jingah Terbang” as well as previous studies. The technique used in data collection and data analysis is text analysis technique. Text analysis techniques are used to describe the ecological wisdom values contained in Bakumpai Dayak folklore through an eco-critical approach and the relationship between Bakumpai Dayak folklore and the surrounding environment. The results of the analysis are presented in the form of a narrative text that explains the relationship between the surrounding environment and folklore. Then verification and conclusion are carried out, namely checking the data that has been collected and analyzed again. Based on the results of the study it was found that in the Bakumpai Dayak folklore